Accidental Entrapment of Electrical Mapping Catheter by Chiari's Network in Right Atrium during Catheter Ablation Procedure - Sakamoto, Atsushi (Case Rep Cardiol, 2016)
A 78-year-old male was admitted to our hospital due to frequent palpitation. His electrocardiogram (ECG) presented regular narrow QRS tachycardia with 170 bpm, and catheter ablation was planned. During electroanatomical mapping of the right atrium (RA) with a multiloop mapping catheter, the catheter head was entrapped nearby the ostium of inferior vena cava. Rotation and traction of the catheter failed to detach the catheter head from the RA wall. Exfoliation of connective tissue twined around catheter tip by forceps, which were designed for endomyocardial biopsy, succeeded to retract and remove the catheter. Postprocedural echocardiography and pathologic examination proved the existence of Chiari's network. The handling of complex catheters in the RA has a potential risk of entrapment with Chiari's network.